A coal burst model based on roof vibration and coal slippage. Issue 4 (October 2020) - Han, J; Jia, D; Cao, C; Zhu, Z; Li, Y
Abstract: Rock burst poses a serious threat to mining, and its mechanism still needs to be studied. Statistics show that more than 85% of rock bursts occur in mining roadways. The authors investigated the mechanism of rock burst in the roadways by creating a finite elastic long beam dynamic model in longwall mining based on the elastic foundation theory. In this study, the fracture failure of the basic roof and the related dynamic effects are analyzed. The results indicate that the occurrence of the free vibration of the basic roof is caused by fracturing during the first face advance. It is also found that the vibration frequency increases and the period decreases with the increase in roof thickness. Furthermore, the strength and elastic modulus increase with the increase in roof hardness. The effect of a thick, hard roof on the coal mass is mainly reflected in the vibration of the roof above the coal seam. During free vibration of the roof, the stress applied by the roof on the coal mass decreases. Under the action of horizontal stress, the coal mass slips along the interface between the roof and coal mass, which may result in rock burst. The mode of the basic roof vibration and the viscoelastic properties of the coal mass significantly influence the vibration–slippage impact. With the increase in the strength, thickness, and horizontal stress of the roof, the possibility of sliding between the coal seam and the roof also increases, which may potentially result in rock burst. This mechanism may explain the occurrence of rock burst in large-scale coal bodies that move out in the roadway, which could provide a reference for the prevention and control of such phenomena.